تقییم نوعیة میاه خزان الحبانیھ باستخدام تقنیات الاستشعار عن بعد ونظم المعلومات الجغرافیھ - nan, nan; nan, nan; nan, nan (Iraqi Journal of Civil Engineering, 2008)
In this study remote sensing was employed with Geographical Information System (GIS) for study the hydrochemistry properties for Habania Lake that is located on Euphrates river, where the use of traditional methods are not fulfill the demands for study quality and situation of water of great areas which need enough time and money . Analytic study was performed on hydrochemical aspect through samples of store water and make physical and chemical water tests with GIS to product layers represent place distribution nature of these elements on the whole area of reservoir through the use of satellite image. The present study concluded that the use of remote sensing , geographic information system and analytic study for samples was employed to study quality and situation of water .